Short-Term Efficacy of Pulsed Electromagnetic Field Therapy on Pain and Functional Level in Knee Osteoarthritis: A Randomized Controlled Study - Duygu Geler Külcü,; Gülçin Gülşen,; Elif Çiğdem Altunok, (Archives of Rheumatology, 2009)
Objective: We aimed to determine the efficacy of pulsed electromagnetic field therapy on pain and functional level in knee osteoarthritis when compared to therapeutic ultrasound (US) and controls. Material and Methods: Forty-five patients with knee osteoarthritis (mean age: 63.5±10.2 years) were randomly assigned to three groups. The first group received pulsed electromagnetic field therapy (frequency: 2 Hz, 100 Hz, 25 Hz consecutively, 35 minutes/ session), the second group received therapeutic US (frequency: 1 MHz, power: 1.5 watt/cm2 continuously, 10 minutes/session) and the third group served as the no- treatment control group. Evaluations were done at baseline and at the end of the treatment (third week). Assessment parameters were pain, stiffness and functional level scores of the Western Ontario and McMaster Universities (WOMAC) questionnaire and pain severity evaluated by Visual Analog Scale (VAS) (0-10). Results: VAS (p=0.005), WOMAC pain score (p=0.001), WOMAC joint stiffness score (p=0.027) and WOMAC functional level score (p=0.003) significantly improved in the first group. VAS (p=0.001), WOMAC pain scores (p=0.008), WOMAC stiffness scores (p=0.012) and WOMAC functional level (p=0.004) scores significantly improved in the second group as well. No change was observed in any assessment parameter in the third group (p>0.05). There were differences between groups regarding the percent change in VAS scores (p<0.001), WOMAC pain scores (p<0.001), WOMAC joint stiffness scores (p=0.013) and WOMAC functional level scores (p<0.001) after the treatments. Conclusion: Both the pulsed electromagnetic field and therapeutic US were significantly more effective than no treatment. The pulsed electromagnetic field may be applied as an effective and alternative therapy approach in knee osteoarthritis. (Turk J Rheumatol 2009; 24: 144-8)